COVID stress syndrome: Concept, structure, and correlates. Issue 8 (5th July 2020) - Taylor, Steven; Landry, Caeleigh A.; Paluszek, Michelle M.; Fergus, Thomas A.; McKay, Dean; Asmundson, Gordon J. G.
Abstract: Background: Research shows that the COVID Stress Scales have a robust multifactorial structure, representing five correlated facets of COVID‐19‐related distress: (a) Fear of the dangerousness of COVID‐19, which includes fear of coming into contact with fomites potentially contaminated with SARSCoV2, (b) worry about socioeconomic costs of COVID‐19 (e.g., worry about personal finances and disruption in the supply chain), (c) xenophobic fears that foreigners are spreading SARSCoV2, (d) traumatic stress symptoms associated with direct or vicarious traumatic exposure to COVID‐19 (nightmares, intrusive thoughts, or images related to COVID‐19), and (e) COVID‐19‐related compulsive checking and reassurance seeking. These factors cohere to form a COVID stress syndrome, which we sought to further delineate in the present study. Methods: A population‐representative sample of 6, 854 American and Canadian adults completed a self‐report survey comprising questions about current mental health and COVID‐19‐related experiences, distress, and coping. Results: Network analysis revealed that worry about the dangerousness of COVID‐19 is the central feature of the syndrome. Latent class analysis indicated that the syndrome is quasi‐dimensional, comprising five classes differing in syndrome severity. Sixteen percent of participants were in the most severe class and possibly needing mental health services. Syndrome severity was correlated with preexisting psychopathology and with excessive COVID‐19‐related avoidance, panic buying, and coping difficulties during self‐isolation. Conclusion: The findings provide new information about the structure and correlates of COVID stress syndrome. Further research is needed to determine whether the syndrome will abate once the pandemic has passed or whether, for some individuals, it becomes a chronic condition.